Judicial Activism: The Impact of Judicial Activism on Human Rights and Democracy (Journal of Advances and Scholarly Researches in Allied Education, 2017)
There is no limited scope for judicial activism. It is used to look at the issues and to implement what is good for society as a whole. This is important to the fact that Justice, 'rich or poor, strong or weak,' is for all, that Karma even has been assigned to the King and Queen with the responsibility to bring righteousness. The research paper concentrates on the expansion in Indian democracy of judicial activism. In order to offer good justice, the judicial activism in India had touched practically all aspects of life. Often the right to judicial review and legal activism serves to defend the weaker sector of society by simply filling up social interest lawsuits or public interest disputes. Judicial action in executive and legislative matters has given society the upper hand in obtaining justice on several occasions. Judicial system is a way to provide 'justice' to everyone and to take all appropriate measures to preserve the JUSTICE interest. Legal basis of judicial activism for inclusion into fundamental rights into the Indian constitution. The preservation of the role of the judiciary is one of the important ways of safeguarding human rights. Judicial standards have an important beneficial effect on people's lives and on achieving the goals of the government. These standards can also ensure that people and their government, on the other hand, and the members of the international community, have a better knowledge of the relationship they have. Furthermore, big countries, such as the United States, are highly responsible for promoting human rights by virtue of their international weight and technical progress. In cases where citizens in the Middle East are willing to help promote human rights and demonstrate real intents to spread peace and stability, large countries should play an active part. They must also play an active role.